Determination of the influence of hydraulic load of centrifugal pump on coordinates of asynchronous frequency-controlled electric drive - O. A. Lysenko (Омский научный вестник, 2023)
The article considers the construction of a simulation model of an electrical complex including an asynchronous electric motor with frequency regulation, driving a centrifugal pump. Fluid pumping stations based on centrifugal pumps with asynchronous electric drives controlled by frequency converters are widely used, which makes the work relevant. Obtaining the dynamic characteristics of these drives makes it possible to understand the relationship of energy distribution, as well as to coordinate the operating modes of its main parts. For this purpose, a simulation model of the electric drive of the liquid pumping station is developed. This simulation model is used to carry out numerical experiments of the system, which includes the power channel of the electric drive, as well as the control system. Simintech software product is used as a modeling environment. In the work, transient processes of the coordinates of the electric drive are obtained under the influence of both the hydraulic load and the power supply. The influence of the hydraulic resistance of the pressure pipeline and static back pressure on the mechanical characteristic of the moment of resistance of the electric drive as a whole is shown. The considered approach for calculating the characteristics makes it possible to evaluate the mutual influence of the coordinates of various physical nature of centrifugal pump installations with an asynchronous frequency-controlled electric motor on each other.